Ubuntu leadership and employee engagement in mining: The moderating role of safety culture - Mpho B. Nelwamondo; Gavin Price (SA Journal of Human Resource Management, 2025)
Orientation: This study explored the influence of Ubuntu leadership on employee engagement in South Africa’s mining industry, with a focus on the moderating role of safety culture.